From “safe” to “brave” spaces: pedagogical practices of exclusion to promote inclusion within & beyond skateboarding - Petrone, Robert; Beal, Becky (Frontiers in Sports and Active Living, 2024)
Through interviews with key stakeholders within skateboard organizations that explicitly attend to issues of diversity, access, and equity, this article explores pedagogical practices that undergird these organizations' programming for justice. More specifically, this article focuses on the interplay between the implementation of practices of exclusion to promote, ultimately, inclusion. In theorizing this pedagogical approach, this article discusses how notions of "brave spaces" work in tandem with ideas and practices of cultivating "safe spaces" to work toward social transformation within and beyond skateboarding.